2021
DOI: 10.1007/s11071-021-06610-0
|View full text |Cite
|
Sign up to set email alerts
|

Causal coupling inference from multivariate time series based on ordinal partition transition networks

Abstract: Identifying causal relationships is a challenging yet crucial problem in many fields of science like epidemiology, climatology, ecology, genomics, economics and neuroscience, to mention only a few. Recent studies have demonstrated that ordinal partition transition networks (OPTNs) allow inferring the coupling direction between two dynamical systems. In this work, we generalize this concept to the study of the interactions among multiple dynamical systems and we propose a new method to detect causality in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Namely, we used Granger causality (GC) [59] and ordinal partition transition networks (OPTN) [50, 51] as two methods of causality inference based on different mathematical principles: while GC measures are valid only for linear interactions, OPTN-based causality measures are sensitive to both linear and nonlinear ones; hence, their combination provides complementary information about statistically inferred coupling. As shown Figure 2D , the GC values demonstrated that the bridge increased the causal relationship between CA3 and CTX in the two directions of the loop (CA3-to-CTX – CTRL1: 0.05 ± 0.01; bridge: 0.44 ± 0.06; CTRL2: 0.05 ± 0.02; one-way ANOVA, F(df): 44.47(2), p < 0.001 bridge vs both CTRLs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Namely, we used Granger causality (GC) [59] and ordinal partition transition networks (OPTN) [50, 51] as two methods of causality inference based on different mathematical principles: while GC measures are valid only for linear interactions, OPTN-based causality measures are sensitive to both linear and nonlinear ones; hence, their combination provides complementary information about statistically inferred coupling. As shown Figure 2D , the GC values demonstrated that the bridge increased the causal relationship between CA3 and CTX in the two directions of the loop (CA3-to-CTX – CTRL1: 0.05 ± 0.01; bridge: 0.44 ± 0.06; CTRL2: 0.05 ± 0.02; one-way ANOVA, F(df): 44.47(2), p < 0.001 bridge vs both CTRLs.…”
Section: Resultsmentioning
confidence: 99%
“…Taken's embedding theorem [52] was used to reconstruct the phase space and obtain the ordinal patterns. For phase space reconstruction, the embedding delay was chosen based on auto mutual-information [53], whereas the embedding dimension was set to 3 based on the data length (200000 samples/window) [51,53,54]. For each time window, the causality was tested for delays ranging from 1 to 100 ms in 1-ms steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many approaches for causal inference have been proposed in the literature, based of model reconstruction, information theory, phase-space reconstruction, nonlinear symbolic analysis, machine learning, etc. (Granger 1969;Schreiber 2000;Baccala and Sameshima 2001;Eichler et al 2003;Sugihara 2012;Runge 2018;Siyang Leng et al 2020;Subramaniyam et al 2021;Huang et al 2020). These approaches have different mathematical hypotheses and computational complexity, and they differ considerably in their capability to detect genuine couplings (Krakovska et al 2018).…”
Section: Introductionmentioning
confidence: 99%